Safety of gadoxetate disodium: results from six clinical phase IV studies in 8194 patients. (November 2016) - Endrikat, Jan; Kim, So Yeon; Sakaguchi, Toshiaki; Dohanish, Susan; Breuer, Josy
Background: Safety data on routine clinical use of gadoxetate disodium for liver magnetic resonance imaging (MRI) is not reported yet. Purpose: To assess the safety profile of gadoxetate disodium for liver MRI in the routine clinical setting. Material and Methods: Six multicenter studies were performed in Europe, USA, Australia, and Asia to evaluate the safety and efficacy of gadoxetate disodium (Primovist®/Eovist®) enhanced liver MRI. Patients received a single intravenous bolus injection of the standard approved dose of 0.025 mmol/kg body weight (0.1 mL/kg). The number of patients, the characteristics of adverse events, related adverse events, and serious adverse events were analyzed. Results: A total of 8194 patients were included in the database. A total of 141 patients (1.7%) reported 230 AEs of which 129 were considered being related to the use of gadoxetate disodium by the investigators. None of the AEs in the pediatric population ( n = 52) were related. The most frequent AEs independent of relationship to the drug included dyspnea (25/0.31%), nausea (22/0.27%), liver disorders (13/0.16%), and renal disorders (9/0.11%). Nine related SAEs were recorded. No patient died during the studies. Conclusion: Gadoxetate disodium for liver MRI is safe and well tolerated in the routine clinical setting.